Acquisition of L2 English spatial deixes by Arabic-speaking children - Alothman, Hissah Nasser; Alsager, Haroon N. (Frontiers in Psychology, 2022)
Deictic words are considered the earliest words which children acquire at the stage of two-word-utterance. However, mastering them like adults may take more time. This paper investigates how L2 children comprehend and produce English spatial deixis ‘here’, ‘there’, ‘this’, and ‘that’ by observing and documenting their responses and reactions in hide-and-seek game. It also aims to find out the children’s obstacles in acquiring these words, such as proximity bias and egocentrism. The subjects are Arabic children of ages four, five, and six who acquire English as a second language in international schools in Riyadh, Saudi Arabia. They performed two types of tasks: comprehension task and production task. Both tasks contained two trials: same perspective and the different perspective. Based on the results, children did better in comprehending the spatial deixis than in producing them. Moreover, the results showed that there was no proximity bias happened with children in this study. In addition, the results of the two trials in both tasks illustrated that changing the deictic center improves with age. Although the study provides some significant results, there should be an increase in the number of the samples in order to make the results generalized.